The cytotoxic and antiproliferative effects of gamavuton- 0 in rat basophilic Leukemia cells - Agung Nugroho (Indonesian Journal of Pharmacy, 2009)
Gamavuton-0 (GVT-0), also named as 1,5-bis(4’-hydroxy-3’-methoxyphenyl)-1,4-pentadiene-3-one is a 1,5-diphenyl-1,4-pentadiene-3-one analog of curcumin by modifying the center site of curcumin leading to 1,4- pentadiene-3-ones to maintain the hydroxy moiety at aromatic rings which are responsible for its biological activities. Curcumin has been reported to have potent anticarcinogenic effects. Besides, curcumin was found to induce apoptosis in human Leukemia cells. In our study, we investigated the cytotoxic and antiproliferative effects of gamavuton-0 in rat basophilic leukemia cells. Cell viability was determined by WST-1 assay. In brief, tetrazolium salts were cleaved to formazan by cellular enzymes of viable cells, determined by colorimetric methods with a microplate (ELISA) reader at 450 nm.In the present study, we evaluated cytotoxic and proliferative effects of GVT-0 in rat basophilic leukemia cells. In the study, GVT-0 induced rat basophilic leukemia cells death in a dose-dependent manner after overnightincubation. GVT-0 also impaired the content of histamine and b-hexoaminidase enzyme in cells. However, the cytotoxic effect of GVT-0 (IC50 : 43,67 mM) was less potent than this of curcumin (IC50 : 29,14 mM). GVT-0 (1 mM) also showed a significant inhibition of cell growth after 48 and 72 hr. Its fact indicates that GVT-0 could prolong the cells doubling time. These results provide useful information to guide the development of new synthetic compounds for the treatment of cancer diseases.Key words : gamavuton-0, curcumin, cancer, cytotoxic, antiproliferative